Impact and optimal timing of local therapy addition in borderline resectable or locally advanced pancreatic cancer after FOLFIRINOX chemotherapy - Kangpyo Kim; Hee Chul Park; Jeong Il Yu; Joon Oh Park; Jung Yong Hong; Kyu Taek Lee; Kwang Hyuck Lee; Jong Kyun Lee; Joo Kyung Park; Jin Seok Heo; Sang Hyun Shin; Ji Hye Min; et al. (Clinical and Translational Radiation Oncology, 2024)
Background: To evaluate the efficacy and optimal timing of local treatment in patients with borderline resectable (BR) or locally advanced pancreatic cancer (LAPC) treated with upfront FOLFIRINOX. Method: Between 2015 and 2020, 258 patients with pancreatic ductal adenocarcinoma (PDAC) were analysed. Treatment outcomes were compared between systemic treatment group (ST) and multimodality treatment groups (MT) using Kaplan–Meier curves and log-rank test. The MT were stratified as follows: FOLFIRINOX + radiation therapy (RT) (MT1), FOLFIRINOX + surgical resection (MT2), and FOLFIRINOX + RT + surgical resection (MT3). Results: With median follow-up period of 18 months, the 2-year overall survival (OS) for the ST was 22.0%, and it was significantly worse than MT (MT1, 46.3%; MT2, 65.7% and MT3; 90.2%; P < .001). The 2-year locoregional progression free survival (LRPFS) and overall PFS in ST were 10.7% and 7.0%, which were also significantly lower than those of MT (2-year LRPFS: MT1, 31.8%; MT2, 45.3%; MT3, 81.0%; 2-year overall PFS: MT1, 23.3%; MT2, 35.0%; MT3, 66.3%; P < .001). In time-varying multivariate Cox proportional hazard model, local treatment contributed to better treatment outcomes, with adjusted hazard ratios of 0.568 (95% confidence interval [CI], 0.398-0.811), 0.490 (95% CI, 0.331-0.726), and 0.656 (95% CI, 0.458–0.940) for OS, LRPFS, and overall PFS, respectively. The time window of 11–17 months after FOLFIRINOX appeared to demonstrate the maximal efficacy of local treatments in OS. Conclusions: Adding local treatment in BR/LAPC patients treated with upfront FOLFIRINOX seemed to contribute in improved treatment outcomes, and it showed maximal efficacy in OS when applied 11-17 months after the initiation of FOLFIRINOX. We suggest that administration of sufficient period of upfront FOLFIRINOX may intensify the efficacy of local treatments, and well controlled prospective trials are expected.